Providing Equal Opportunity In Learning: The Role Of The OUM Digital Library In Distance Learning - Zaiton Osman; Sharipah Hanon Bidin (2003)

(untitled)
The relevance of any library to its parent organization depends on the need for it. In the case of a university library, if the library is as described in the professional literature as being at the heart of teaching and learning – then the need for it must exist in the teaching and learning environment within which it operates. The need to view the relevance of the library within the educational context is important in order to avoid an ‘isolationist’ approach to library development. It is easier to understand the role of the library seen against the background of the prevailing concept of education, aims and objectives of education, teaching-learning objectives and strategies, etc. In the case of the Digital Library, it is necessary to understand the democratisation process of higher education, the concept of the Open University and its core activities so that any discussion of its role can be done in the proper context and from a meaningful perspective.